Critical-sized mandibular defect reconstruction using human dental pulp stem cells in a xenograft model-clinical, radiological, and histological evaluation (2020)
Purpose: This research evaluated clinical, histological, and radiological osseous regeneration in a critical-sized bilateral cortico-medullary osseous defect in model rabbits from New Zealand after receiving a hydroxyapatite matrix and polylactic polyglycolic acid (HA/PLGA) implanted with human dental pulp stem cells (DPSCs). Methods: Eight New Zealand rabbits with bilateral mandibular critical-sized defects were performed where one side was treated with an HA/PLGA/DPSC matrix and the other side only with an HA/PLGA matrix for 4 weeks. Results: An osseointegration was clinically observed as well as a reduction of 70% of the surgical lumen on one side and a 35% on the other. Histologically, there was neo-bone formation in HA/PLGA/DPSC scaffold and angiogenesis. A bone radiodensity (RD) of 80% was radiologically observed achieving density levels similar to mandibular bone, while the treatment with HA/PLGA matrix achieves RD levels of 40% on its highest peaks. Conclusions: HA/PLGA/DPSC scaffold was an effective in vivo method for mandibular bone regeneration in critical-sized defects induced on rabbit models.